Properties of cement sand brick containing palm oil clinker as partial sand replacement - Mohamad Faiz, Syed Ali (2017)
Palm oil clinker is a by-product of palm oil industry, which normally being dumped abundantly as waste that can caused undesirable effects to our environment sustainability. The amount of waste are expected to increase due to rapid growth of palm oil industry in Malaysia. Due to growth of construction industry in Malaysia, demand toward construction material like sand will also increase. Increase in sand usage will lead to increase in river sand mining activity that can cause ecological imbalance such as channel substrate removal, river bank erosion and sediment suspension. All of this problem has lead researcher to find a possible material replacement for sand and this research focused about palm oil clinker as possible sand replacement material. This research studied the effect of palm oil clinker on properties of cement sand brick that are compressive strength test, flexural strength test and moisture absorption test. The percentage of sand replacement are 10%, 20%, 30% and 40%. All the results were compared with control brick. The testing age are set to specific days, which are 7, 14 and 28 days. All the test were conducted according to ASTM standard for brick. Finding shows that cement sand brick containing 10% of palm oil clinker (POC) replacement provides the best results in terms of compressive strength and flexural strength. However, for water absorption test, plain brick shows a better result.